Biodiesel composition effects on density and viscosity of diesel-biodiesel blend: a CFD study - Maksom, Mohammad Syahadan; Nasir, Nurul Fitriah; Asmuin, Norzelawati; Abd Rahman, Muhammad Faqhrurrazi; Khairulfuaad, Riyadhthusollehan (Penerbit Akademia Baru, 2020)
Biodiesel can be prepared by transesterification process, with methyl ester and glycerol as the final products. After the transesterification process, diesel and biodiesel are blended in mixing tank at certain temperature for a period of time until the mixture achieves the visual inspection, before it can be applied to CI engine. However, there are lacks of information regarding the mixing effects on the density and viscosity of the biodiesel during the blending process. Therefore, this project is aimed to study the effects of different blending ratio on the density and viscosity of diesel biodiesel blend using Computational Fluid Dynamic (CFD) ANSYS Fluent software. It is also aimed to analyse the mixing pattern of blending process either both diesel and biodiesel are uniformly mix. By using CFD software, volume fraction, density and viscosity contours are generated and it is found that the density and viscosity has proportional relationship with biodiesel blends composition. The present study confirms previous findings and contributes additional evidence that suggests higher composition for higher density and viscosity.